Konstruksi Citra Sekolah Sunnah di Indonesia (Studi Kasus Konstruksi Citra Sekolah Sunnah Menurut Perkumpulan Komunikasi Sekolah Sunnah Indonesia (ASESI) - Rafika Hani (LONTAR: Jurnal Ilmu Komunikasi, 2019)
Nowadays, there are so many emerging Islamic schools in Indonesia. One of them is theestablishment Islamic school which is the Islamic religious education based on Al-Qurán and AsSunnah Shahih from Rasululullah Shallallahuálaihiwasallam. This school are known as the SunnahSchool or school in Manhaj Ahlusunnah waljamaáh, and more often also called as Salafi school.ASESI as a communication forum for sunnah schools in Indonesia see the realities of the phenomenonof sunnah schools in Indonesia. This study uses a qualitative descriptive method with a case studyapproach. Data collection techniques are carried out by observation, interviews, and literature.ASESI process the image construction of sunnah schools in Indonesia. The process consists ofexternalization by looking at the realities that the management of the Sunnah school in Indonesia isstill not well organized. The objectivation process is that ASESI organizes programs to improve theimage of the sunnah school as a school that has a quality sunnah. The internalization process, namelyASESI, means the community's perception of the enthusiasm of the community towards the programscarried out by ASESI.